Valuing Nature for Wellbeing: Narratives of Socio-ecological Change in Dynamic Intertidal Landscapes. (1st August 2021) - Roberts, Erin; Thomas, Merryn; Pidgeon, Nick; Henwood, Karen
Contributing to the cultural ecosystem services literature, this paper draws on the in-depth place narratives of two coastal case-study sites in Wales (UK) to explore how people experience and understand landscape change in relation to their sense of place, and what this means for their wellbeing. Our place narratives reveal that participants understand coastal/intertidal landscapes as complex socio-ecological systems filled with competing legitimate claims that are difficult to manage. Such insights suggest that a focus on diachronic integrity (Holland and O'Neill 1996) within place narratives might offer a route to more socially and culturally acceptable environmental management strategies.